Narrow corridor : states, societies, and the fate of liberty - Acemoglu, Daron; Robinson, James A.; Penguin Random House (UK: Penguin Random House, 2019)
"A crucial new big-picture framework that answers the question of how liberty flourishes in some states but falls to authoritarianism or anarchy in others--and explains how it can continue to thrive despite new threats"--
Includes bibliographical references (pages [499]-541) and index.
Keywords: Liberty; State, The; Power (Social sciences) -- Political aspects; Direct democracy; Decentralization in government; Executive power; Violence -- Political aspects